Gene expression profiling with principal component analysis depicts the biological continuum from essential thrombocythemia over polycythemia vera to myelofibrosis - Skov, Vibe; Thomassen, Mads; Riley, Caroline H.; Jensen, Morten K.; Bjerrum, Ole Weis; Kruse, Torben A.; Hasselbalch, Hans Carl; Larsen, Thomas Stauffer (Experimental hematology, 2012)
The recent discovery of the Janus activating kinase 2 V617F mutation in most patients with polycythemia vera (PV) and half of those with essential thrombocythemia (ET) and primary myelofibrosis (PMF) has favored the hypothesis of a biological continuum from ET over PV to PMF. We performed gene expression profiling of whole blood from control subjects (n = 21) and patients with ET (n = 19), PV (n = 41), and PMF (n = 9) using DNA microarrays. Applying an unsupervised method, principal component analysis, to search for patterns in the data, we demonstrated a separation of the four groups with biological relevant overlaps between the different entities. Moreover, the analysis separates Janus activating kinase 2-negative ET patients from Janus activating kinase 2-positive ET patients. Functional annotation analysis demonstrates that clusters of gene ontology terms related to inflammation, immune system, apoptosis, RNA metabolism, and secretory system were the most significantly deregulated terms in the three different disease groups. Our results yield further support for the hypothesis of a biological continuum originating from ET over PV to PMF. Functional analysis suggests an important implication of these gene ontology clusters in the pathogenesis of these neoplasms and in disease evolution from ET over PV to PMF.